2017
DOI: 10.1080/10872981.2017.1301697
|View full text |Cite
|
Sign up to set email alerts
|

The state of leadership education in US medical schools: results of a national survey

Abstract: Over the past two decades, there have been increasing calls for physicians to develop the capabilities to lead health care transformation. Many experts and authors have suggested that leadership education should begin during medical school; however, little information exists regarding the presence or nature of undergraduate medical education leadership curricula in the USA. This study sought to determine the prevalence of formal leadership education in US undergraduate medical schools, as well as the delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…However, explicit leadership education, training, and development within classic medical school setting is largely missing. In recent years, this deficit has been recognized by the medical profession (Neely, Clyne, & Resnick‐Ault, ). This recognition was brought to bear by two major reports from the Quality of Healthcare in America Project conducted by the Institute of Medicine's (IOM) which sought to address and offer suggestions to mitigate major issues within healthcare including the disturbing fact that nearly 40,000 patients died from medical error every year (Institute of Medicine, ; Kohn, Corrigan, & Donaldson, ).…”
Section: Overview Of Leadership Within the Medical Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…However, explicit leadership education, training, and development within classic medical school setting is largely missing. In recent years, this deficit has been recognized by the medical profession (Neely, Clyne, & Resnick‐Ault, ). This recognition was brought to bear by two major reports from the Quality of Healthcare in America Project conducted by the Institute of Medicine's (IOM) which sought to address and offer suggestions to mitigate major issues within healthcare including the disturbing fact that nearly 40,000 patients died from medical error every year (Institute of Medicine, ; Kohn, Corrigan, & Donaldson, ).…”
Section: Overview Of Leadership Within the Medical Disciplinementioning
confidence: 99%
“…While IPE curriculum is now required, another form of leadership curriculum is gaining steam. This second form is actual leadership courses offered as part of standard medical school curriculum (Neely et al., ; O'Connell & Pascoe, ; Webb et al., ).…”
Section: Student Leadership Education and Developmentmentioning
confidence: 99%
“…Undergraduate medical education (UME) requirements already are extensive and the continuous introduction of new procedures, instruments, medications, and record systems keep adding more to learn. In addition, there is a growing clarion call to add leadership education to UME (Webb et al, 2014;Frich et al, 2015;Neeley, Clyne and Resnick-Ault, 2017;Grunberg et al, 2018). According to the AAMC, leadership is "the most critical component for success (Association of American Medical Colleges)."…”
Section: Problemmentioning
confidence: 99%
“…The results of a national survey of leadership education in US medical schools were published by Neeley and colleagues13 in 2017. Responses were received from 88 of 123 (71.5%) US medical schools, with 48 of 88 (54.5%) participants advising their school had a formal leadership curriculum; however, only a third reported that the curriculum was compulsory.…”
Section: Medical Leadership Evidencementioning
confidence: 99%
“…This also seems to be true for both direct entry and graduate programmes, with few signs of change on the horizon. Authors in the UK,12 USA13 and Australia14 describe the paucity of research in the teaching and assessment of leadership skills training across the continuum of medical education. For many medical schools that do teach leadership, it is often not compulsory, and leadership curricula are developed without measurable student leadership competencies 15…”
Section: Introductionmentioning
confidence: 99%